APAKAH INOVASI PAJAK DAERAH MEMPERLAMBAN DAYA INOVASI PEMERINTAH DAERAH DALAM PELAKSANAAN DESENTRALISASI FISKAL? (STUDI DI KABUPATEN SUMBAWA, INDONESIA) - Purwadinata, Subhan; Kaluge, David (Jurnal Ilmu Ekonomi dan Pembangunan, 2017)
The purpose of this study is to objectively review the local tax innovation program on the existence of local government's innovation power to other sector innovation policies in the implementation of fiscal decentralization. Based on previous research, the SoMentari program (socialization, data collection, daily billing) still has not resolved the issue of balanced program policy adjustment for all local government program innovations on the implementation of fiscal decentralization. In an effort to analyze the innovations reviewed in the perspective of the application of SoMentari policy ever applied, the researcher uses an explorative research method approach by trying to find new ideas or relationships. This method is very flexible in the search for ideas and ideas as well as guidance on the conditions and situations related to the issues studied so as to formulate the right policy or strategy. Collect all literature and studies on local tax innovation policies and include secondary data in the form of local tax data and other data related to innovation of other local government programs. After that identified problems ranging from symptoms to basic problems. After further identification, the researcher will classify the problem and reconstruct the local tax and other innovation policies in the perspective of implementing fiscal decentralization. In addition, researchers conducted Focus Group Discussion to some experts who are experts in local tax innovation policy. The results of this study indicate that the local tax innovation program has the potential to slow the innovation of local government in other sectors. The conclusion of this research is that local tax innovation done by local government has not run optimally since there are many other program innovations which require follow up plan from local tax program so that impressed slowing innovation of local government in implementing fiscal decentralization.  Keywords: Regional Innovation, Local Tax, Fiscal Decentralization